NAFTA and the diversification of Mexico's exports: Emprical investigation on the predictions of the heterogeneous firms trade models - Tadashi Ito (Graduate Institute of International and Development Studies, 2008)
Using NAFTA's effect on Mexico's exports as a natural experiment, this paper conducts an empirical analysis on the explanatory power of the two strands of heterogeneous firms trade models: the heterogeneous firms trade (HFT) model and the quality heterogeneous firms trade (QHFT) model. The paper first discusses the common prediction of the two models on new goods' exports and on the contrasting prediction on unit price evolution. An empirical analysis shows a strong supportive evidence on the common prediction, i.e., NAFTA's positive impact on new goods exports from Mexico to the US. The paper then proposes a simple way to check the explanatory power of the models on unit price evolution, and finds no evidence in favour of either model.
Keywords: F14; F15; 330; NAFTA; Exports Diversificaion; Freihandelszone; Exportdiversifizierung; Mexiko